Long noncoding RNA EPB41L4A‐AS1 functions as an oncogene by regulating the Rho/ROCK pathway in colorectal cancer. Issue 1 (17th June 2020) - Bin, Jie; Nie, Shaolin; Tang, Ziyuan; Kang, Anding; Fu, Zhongping; Hu, Yingbin; Liao, Qianjin; Xiong, Wei; Zhou, Yujuan; Tang, Yanyan; Jiang, Jiarui
Abstract: Colorectal cancer (CRC) is one of the most common malignant tumors worldwide. In terms of cancer‐related death, colon cancer ranks second and third among men and women, respectively, and the incidence is increasing annually. Accumulating evidence have indicated that long noncoding RNA (lncRNA) plays an important role in tumorigenesis. In this study, we found that lncRNA EPB41L4A‐AS1 was highly expressed in CRC tissues and was associated with poor prognosis and tumor metastasis in patients with CRC. In vitro studies showed that the knockdown of EPB41L4A‐AS1 inhibited the proliferation, migration, invasion, and epithelial–mesenchymal transition of CRC cells. Mechanically, we found that EPB41L4A‐AS1 may participate in the development of CRC by activating the Rho/Rho‐associated protein kinase signaling pathway. Collectively, these results demonstrated that EPB41L4A‐AS1 can promote the proliferation, invasion, and migration of CRC, and it may be a novel biomarker for the diagnosis and targeted treatment of CRC.